Pediatric Blood Disorders With Central Nervous System Complications - ŞENOL, Feray Ferda (MAS Journal of Applied Sciences, 2023)
Pediatric Hematology Oncology is a broad and complex area that encompasses perturbations of the several-formed elements of the blood and their precursors in the bone marrow, as well as the coagulation-fibrinolytic systems in the plasma, the reticuloendothelial system, and malignancies of the blood and solid tissues and organs. The most common non-malignant blood disorders in adolescents include the various forms of cytopenias, anemias, bleeding and clotting disorders, and hemoglobinopathies. Iron deficiency is the most prevalent nutritional deficiency affecting children and adolescents worldwide. But, anemia occurs frequently in children with cancer. Iron deficiency anaemia is commonly associated with thrombocytosis. Thrombocytopenia, or low platelets, can occur as an isolated finding or in conjunction with a multitude of underlying clinical conditions. Venous thromboembolism result in significant morbidity and mortality in children with cancer. Alpha-thalassemia major is the most common genetic variant of transfusion-dependent thalassaemia seen in the Indian subcontinent, the Mediterranean basin, Southeast Asia and China. Bleeding events still predominate as the diagnostic trigger in children, however, the sites of bleeding vary with age. Bone marrow failure is a rare but life-threatening disorder that usually manifests as (pan)cytopenia. Central nervous system tumors are the most common cancer diagnosed in children after leukemia, accounting for 20% of all pediatric malignancies. Fanconi anemia is an autosomal recessive disease characterized by developmental anomalies, bone marrow failure, cellular sensitivity to DNA cross-linking agents, and increased incidence of both hematologic and solid tumors. This narrative review focuses on the most suggestive symptoms of hematologic disorders with central nervous system complications in childhood.